Transformasi Sistem Pertahanan Siber Indonesia dengan BSSN Sebagai Poros & Motor Penggerak Menuju Angkatan Siber Mandiri di Masa Depan - Adma, Arinaldo; Surbakti, Yusuf Marsel; Sari, Puspita (UI Scholars Hub, 2023)
Abstract Cyber threats are becoming more widespread due to the increasing digitalization in all sectors and entities which include individuals, businesses, and government. To maintain stability, economic growth, and national sovereignty, it is essential for country to have a comprehensive and effective cyber threat prevention and management system. In 2023, Lemhanas proposed a strategy to develop cyber forces as a new branch in the Indonesian national army structure to face the dynamics of the strategic environment. However, the current limitations in digital talent, ICT infrastructure, management systems, and funding pose challenges in implementing this strategy. This research aims to find a middle-way option to strengthen cyber resiliencies within Indonesia’s existing limitations by studying existing literature. The analysis recommends transforming the cyber defense system using the existing organizational posture with BSSN as the main axis. This step can act as a short-term milestone towards developing cyber forces in the medium and/or long term. Keywords: Cyber Threats, National Cybersecurity Defense System, Cybersecurity, Cyber Army, Cyber Transformation